2020
DOI: 10.4314/ahs.v20i4.34
|View full text |Cite
|
Sign up to set email alerts
|

Association between APOC3 polymorphisms and non-alcoholic fatty liver disease risk: a meta-analysis

Abstract: Background and Aim: The apolipoprotein C3 (APOC3) polymorphism has been reported to predispose to non-alcoholic fatty liver disease (NAFLD). However, the results remain inconclusive. This meta-analysis aimed to provide insights into the association between APOC3 polymorphisms and NAFLD risk. Methods: Studies with terms “NALFD” and “APOC3” were retrieved from PubMed, Web of Science, CNKI and Wan- fang databases up to August 1, 2019. Pooled odds ratio (OR) and 95% confidence interval (95% CI) for the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Even during this Covid-19 pandemic, NCDs are forever with thus: cardio-vascular disease nursing care, 21 hypertention, 22 HIV-exposed infants 23 , ECG abnormalities in HIV, 24 left ventricular hypertrophy, 25 epicardial fat, 26 aerobic exercise, 27 insulin resistance, 28 asthma, 29 COPD and sleep, 30 e cigarettes, 31 non- alcoholic liver disease, 32 home care, 33 Bilateral paediatric surgery, 34 self-harm, 35 MRI, 36 osteosarcoma risk, 37 thyroid 38 and gastric esophageal cancer; 39 fibromatosis, 40 prostate cancer, 41 neuro-endocrine tumour, 42 polycystic ovary and vitamin D deficiency, 43 micro RNAs and disease: 44 all will hopefully make us appreciate the burden and effect of this scourge on our people.…”
Section: Ncds: Our Curse Of the Centurymentioning
confidence: 99%
“…Even during this Covid-19 pandemic, NCDs are forever with thus: cardio-vascular disease nursing care, 21 hypertention, 22 HIV-exposed infants 23 , ECG abnormalities in HIV, 24 left ventricular hypertrophy, 25 epicardial fat, 26 aerobic exercise, 27 insulin resistance, 28 asthma, 29 COPD and sleep, 30 e cigarettes, 31 non- alcoholic liver disease, 32 home care, 33 Bilateral paediatric surgery, 34 self-harm, 35 MRI, 36 osteosarcoma risk, 37 thyroid 38 and gastric esophageal cancer; 39 fibromatosis, 40 prostate cancer, 41 neuro-endocrine tumour, 42 polycystic ovary and vitamin D deficiency, 43 micro RNAs and disease: 44 all will hopefully make us appreciate the burden and effect of this scourge on our people.…”
Section: Ncds: Our Curse Of the Centurymentioning
confidence: 99%
“…Specifically, we will elaborate on four specific polymorphisms: PNPLA3, TM6SF2, PEMT, and CHDH, and highlight the dietary patterns/nutritional factors that are associated with their SNPs. Although other genes, such as apolipoprotein C3 (APOC3), and gene choline kinase alpha (CHKA) also seem to play a role in the genesis and development of NAFLD, their connections with nutrition and dietary patterns are still missing [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…[9] At present, genome-wide association studies (GWAS) have demonstrated several conspicuous genetic susceptibility genes such as PNPLA3, SAMM50, PARVB, APOC3, PPAR-γ, NCANCILP2, FABP1, AGTR1, GSTs, which had been verified the crucial roles in the disease onset and progression of NAFLD. [10][11][12][13][14][15] Among them, rs738491, rs2143571, and rs3761472 in the sorting and assembly machinery component 50 homolog (SAMM50) gene were demonstrated to be notably associated with NAFLD susceptibility. [16] Up to now, there have been several reports on SAMM50 gene SNPs and NAFLD susceptibility, but the results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%